Application of TiO2 nanoparticle in photocatalytic degradation of organic pollutants - Singh T.; Srivastava N.; Lal Singh N. (My University, 2025)
Heavy industrialization, specifically in the developing countries, has generated several unwanted environmental pollution. A variety of toxic organic compounds is produced in chemical and petroleum industries, which have resulted in collectively hazardous effects on the environment that needs immediate attention for remediation. Degradation of these pollutants has been tried through the various mechanism, out of which photocatalytic degradation seems to be one of the most promising approaches to reduce environmental pollution specifically in waste water treatment. Photocatalytic degradation has potential for the effective decomposition of organic pollutants due to efficiency to convert light energy into chemical energy. Additionally, the photocatalytic oxidation process is an advanced technique as it offers high degradation and effective mineralization at moderate temperature and specific radiation wavelength. Among various known photocatalysts, TiO2 is regarded as the one of the potential photocatalysts because of its hydrophilic property, high reactivity, reduced toxicity, chemical stability and lower costs. Therefore, the present chapter focuses on the role of TiO2 as the photocatalyst for the degradation of organic pollutants. The general mechanism of degradation of organic pollutants along with properties of TiO2 as the photocatalyst, existing mechanism of degradation via TiO2 was explained. The possible approaches to enhance degradation via TiO2 nanoparticle along with existing bottlenecks have been also discussed. © 2016 Trans Tech Publications, Switzerland.